The Influence of Occupational Health and Safety (OHS) programs on employee productivity: Empirical evidence from a state-owned electric utility In North Sumatra, Indonesia - Taufik Hidayat; Masdania Zurairah; Asmara Sari Nasution (Program Studi Teknik mesin, Fakultas Teknik, Universitas Al Azhar Medan, 2026)
Background: Occupational Health and Safety (OHS) programs are critical determinants of workforce productivity in high-risk industrial environments. Despite extensive literature on OHS, empirical evidence specifically examining its quantified effect on employee productivity in Indonesian state-owned power utilities remains scarce, constituting a significant research gap. Objective: This study investigates the simultaneous and partial effects of occupational health (X1) and occupational safety (X2) programs on employee productivity (Y) at PT PLN (Persero) Pembangkitan Sektor Belawan, Medan, Indonesia. Methods: A quantitative-associative cross-sectional design was employed. Data were collected via validated Likert-scale questionnaires from a census sample of 85 permanent employees. Multiple linear regression analysis was conducted using SPSS 21.0, supplemented by validity (Pearson r), reliability (Cronbach’s ?), and normality tests. Results: Reliability coefficients ranged from ?=0.655 to ?=0.822, confirming instrument consistency. The simultaneous F-test yielded F(2,82)=231.212 (p<0.001), explaining 84.9% of variance in productivity (R²=0.849). Occupational health exerted a dominant positive partial effect (?=0.828, t=13.412, p<0.001), while occupational safety also contributed significantly (?=0.124, t=2.016, p=0.047). Conclusion: Both OHS dimensions positively and significantly predict employee productivity, with occupational health being the stronger driver. These findings provide actionable evidence for policymakers and OHS managers in energy-sector utilities across developing economies. Novelty: This study is the first to quantify the differential dominance of occupational health over safety in predicting productivity within Indonesia’s state power-generation sector, extending OHS theory into an emerging-market context.